KOMBINASI GNU PRIVACY GUARD DAN HAMMING DISTANCE UNTUK KEAMANAN EMAIL SERTA JALUR SERTIFIKASI - Matheus Supriyanto Rumetna (LPPM Poltek ST Paul, 2021)
Email is one of the advanced features related to electronic correspondence by utilizing internet technology. One of the reasons why many people use email, because it provides an easy and fast way to send information. But email is also inseparable from security problems such as being intercepted, forged, infiltrated by viruses, spamming, mailbombing, mail relay. But email confidentiality is threatened not only by hackers, but by system administrators themselves. One way to overcome this is to encrypt the email using Gnu PG. So, the focus of this research is on email security issues as well as to create a trusted certification path. In this study, an authentication protocol is proposed that makes the certificate repository size as log2 N using the concept of Hamming Distance, convincingly to create a secure certification path from one node to another. It also provides a public key management mechanism for issuing, updating and revoking certificates between nodes based on Hamming Distance.